Pembentukan Karakter Siswa Di Smp At Tajdid Pondok Pesantren Modern Muhammadiyah Kabupaten Blora Tahun 2015 - Furqony, Ahmad; , Dr. Sudarno Shobron, M.Ag (2016)
SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora advancing good value instilling, tahfidzul qur‟an, understanding book and strange language masteries. It is gone upon on continues aught system so it is not possible gets despite School of Quranic points already been planted out and gets up, so background is integrated character education at in it. Problem formula in observational it there is three, namely: a. How is education model at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora?; b. Molded whatever character educationally at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora?; c ) Whatever supporting factors and character forming resistors educationally at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora? To the effect this research it is Cast molded whatever character and effloresce educationally at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora. There is tech even data collecting utilizes to methodic observation, interview, and documentation. Result observationaling to point out that pesantren's Education Model at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora consisting of formal Education, sorogan, bandongan, muhadharoh and muhawarah, tasyji ' ul lughoh, ta ' limul quro ‟. In common is said that school of Quranic education at SMP At Tajdid is Modern Islamic School Quranic of Muhammadiyah Blora Regency performed according to steps, approach, and forming point principles santri's characters. Molded character educationally pesantren ranges various composition kind assess, for example religion point, moral point, common points. There is character even that consisting of 39 (thirty nine) point, namely: taqarrub, istiqa>mah, patient, tawakal, sincere, atonement , recitation, khusyu>', laugh>dhu ', mura>qabah, tasamuh , religious, on the level, tolerance, discipline, hard-earned, creative, independent, democratic, inquiring taste, nationalistic spirit, country love, pricing achievement, brotherly / communicative, placating love, like to read, environmental care, social care, accountability, love to God and truth, trust, held dear and decent, affection, care, and collaboration , self-confident, creative, and prohibition gives up, justice, and leadership soul. Supporting factor, cover: a ) being accomplished of it components that theoretically prop school of Quranic education performing; b ) most actually learning media those are equal to and propping happens it school of Quranic education process; c ) santri's get spirit in follow school of Quranic education process progressively increases. There is factor even resistor covers: a ) Still felt by its reducing supporting facility as book of library supporters; b ) were accomplished its building mediums comprehensif.; c ) Deep determine strategy educations not teacher sparses perceives handicaps, it because of umpteen factor; d. ) gets bearing with equipments medium also been felt extant one haven't qualification.